Research on thermal stress fracture performance of low-temperature asphalt concrete in castel high altitude area - Ke, Wenhao; Lei, Yu; Chen, Tuanjie; Cao, Haibo (Frontiers in Earth Science, 2023)
The temperature in the southwest Castel highland area is relatively low, and the asphalt concrete on the road surface is in a low-temperature state all year round. Strong ultraviolet radiation will interfere with the material and cause it to fracture and damage. This paper uses a low-temperature bending test and thermal stress constrained specimen test (TSRST) to test the low-temperature performance of asphalt mixtures with different gradation and asphalt types under different ultraviolet (UV) aging conditions. Existing studies are mainly based on asphalt aging, which cannot take into account the interactions between the binder and aggregate phases during aging. This paper analyzes the correlation between test indexes after UV aging and asphalt mixture parameters, as well as the impact of UV on asphalt mixtures, and the mechanical strength prediction model was established. The results indicate that when the aging time is less than 2 months, the low-temperature performance degradation rate of the asphalt mixture first accelerates and then gradually slows down. The degree of influence of ultraviolet radiation on different graded asphalt mixtures is in descending order: stone asphalt concrete, AC 16 asphalt concrete, and AC-13 asphalt concrete. The relationship between fracture thermal stress and asphalt mixture parameters is strong. It is suggested that the appropriate equivalent outdoor aging time is 2 months in the low-temperature performance test of asphalt mixture after UV aging. At the point when there is no UV test condition, the worth acquired by the test is prescribed to consider the UV aging attenuation coefficient, and the matrix asphalt can allude to 0.84; modified asphalt has a value of 0.9. This article is of great significance for guiding the research on thermal stress fracture of low-temperature asphalt concrete in Castel high-altitude areas.